2005
DOI: 10.1051/0004-6361:20052973
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of planetary nebulae and HII regions in the dwarf galaxies Sextans A and B from deep VLT spectra

Abstract: Spectroscopic observations obtained with the VLT of one planetary nebula (PN) in Sextans12 + log (O/H) = 7.6 ± 0.2 in Sextans A, and 7.8 ± 0.2 in Sextans B. For the five PNe of Sextans B, we find that 12 + log (O/H) = 8.0 ± 0.3, with a mean abundance consistent with that of H  regions. The only PN known in Sextans A appears to have been produced by a quite massive progenitor, and has a significant nitrogen overabundance. In addition, its oxygen abundance is 0.4 dex larger than the mean abundance of H  regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 46 publications
8
59
0
Order By: Relevance
“…1 (Lee et al 2006) and Sextans B (Kniazev et al 2005;Magrini et al 2005). The face value of the average O/H is also consistent with those found by previous studies of IC10 by Hodge & Lee (1990) and Richer et al (2001).…”
Section: Results-i: Ic10's Enrichment Is Non-homogeneously Distributedsupporting
confidence: 91%
“…1 (Lee et al 2006) and Sextans B (Kniazev et al 2005;Magrini et al 2005). The face value of the average O/H is also consistent with those found by previous studies of IC10 by Hodge & Lee (1990) and Richer et al (2001).…”
Section: Results-i: Ic10's Enrichment Is Non-homogeneously Distributedsupporting
confidence: 91%
“…For instance, in some very metal poor galaxies it has been found that oxygen abundances of PNe (and apparently also Ne) are higher than the average value of H II regions. Such is the case in the only PN known in Sextans A (Kniazev et al 2005;Magrini et al 2005), in the 8 PNe studied in NGC 3109 by Peña et al (2007), in a large fraction of PNe in the SMC and in a small but significant fraction in the LMC (Leisy & Dennefeld 2006 (Hernández-Martínez et al 2009, in preparation), we will present a more detailed grid of models and a deeper discussion on this subject.…”
Section: Introductionmentioning
confidence: 98%
“…The present work is part of our study of the structure and evolution of Local Group and nearby galaxies through the spectroscopy of their emission-line populations (see, e.g., Magrini et al 2005;Gonçalves et al 2007;Magrini & Gonçalves 2009;Gonçalves et al 2012Gonçalves et al , 2014Stanghellini et al 2015). In this framework, we have carried on a deep spectroscopic campaign with the multi-object spectrograph GMOS@Gemini-South telescope of the strong-line emitters of NGC 55, as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%